Design and Geometric Transformations of Koch Curve Monopole Antennas - Jamil, A.; Rafique, K.; Idrees, M. D.; Rajput, A. S.; Abdullah, A.; Saand, A. S. (Engineering, Technology & Applied Science Research, 2022)
In this paper, a modified Koch curve monopole antenna is proposed for the dual-band Wireless Local Area Network (WLAN) and its performance has been compared with the conventional printed Koch-curve monopole antenna. Both the antennas have been contrived, and their simulated return loss and radiation pattern results have been validated with the measurements. Antenna #1 is designed on the geometrical basis of a conventional Koch-curve monopole antenna. Moreover, the shape of antenna # 1 is bent with a two-step rotation process to yield antenna #2. There are two advantages to this geometrical modification: Firstly, the unique rotation in antenna #2 has further increased the mutual coupling between the segments of the Koch-curve geometry, and thus improved the impedance matching. Secondly, due to its geometric configuration that enhanced its ground plane size, the proposed antenna #2 has been able to demonstrate consistent simulation and measurement results. The compact ground plane in antenna #1 has been identified as the primary reason for the disagreement between the simulated and measured return loss results. The presented antennas have also been studied for the variation of indentation angles: θ=30 and θ=60.